Identity‐based encryption resilient to continuous key leakage. (1st September 2019) - Zhou, Yanwei; Yang, Bo; Mu, Yi; Wang, Tao; Wang, Xin
Abstract : Leakage of private information has become a threat to the security of computing systems. It has become a common security requirement that a cryptography scheme should withstand various leakage attacks, even the continuous leakage attacks. However, in the current constructions on the (continuous) leakage‐resilient identity‐based encryption (CLR‐IBE) scheme, the leakage parameter is a fixed value. Aiming to solve these problems, in this study, the authors show how to construct the CLR‐IBE scheme, and the adaptive chosen‐ciphertext attacks security of proposed construction can be proved in the standard model. To further improve the practicability of CLR‐IBE scheme, they design an improved IBE scheme with continuous leakage amplified property, and the leakage parameter has an arbitrary length.